Giant pleomorphic adenoma of parotid gland - Lakshmi, A. Bhagya; Rao, G. Santa; Uma, P.; Devi, P. Urmila (International Journal of Research in Medical Sciences, 2017)
Salivary gland tumors are rare, comprising less than 3% of all neoplasia of head and neck region. Pleomorphic adenomas are the most common benign neoplasms of the parotid gland. The vast majority are 2-6cms in size, when resected. Untreated pleomorphic adenomas can enlarge in size and weigh several kilograms. There are only few cases of giant pleomorphic adenomas reported in the literature. Here we present one of such case.